YM v LB (465/09) [2010] ZASCA 106 (17 September 2010) - Llewelyn Gray Curlewis (Obiter, 2021)
In this matter, which resulted in an enquiry by the Supreme Court of Appeal and ultimately a unanimous decision, the facts were the following: the appellant, Mrs Y M (M) appealed against an order that she and her minor daughter (Y) submit to DNA testing to determine whether Mr L B (B), the respondent, was the biological father of Y. The order was sought by B, who also claimed that, if the tests proved that he was indeed the father, he should be given full parenting rights. The North Gauteng High Court (Pretoria) (Murphy J sitting as court of first instance), ordered that M submit herself and Y to DNA tests within 30 days of the date of the order, and postponed the other relief sine die. The Supreme Court of Appeal granted leave to appeal. On appeal, B filed no heads of argument, and nor was there any appearance on his behalf.